In situ synthesis of nitrogen- and sulfur-enriched hierarchical porous carbon for high-performance supercapacitor - Mehare, Rupali S.; Ranganath, Suresha P.; Chaturvedi, Vikash; Badiger, Manohar. V.; Shelke, Manjusha V. (Energy & Fuels, 2018)
In this work, we present a simple and facile method for the nitrogen (N)- and sulfur (S)- doped porous three-dimensional (3D) spongelike carbon materials via direct pyrolysis of N and S containing polymer N,N'-methylene-bis-acrylamide cross-linked poly(acrylamide-co-2-acrylamido-2-methyl-1-propanesulfonic acid) at varying temperatures under inert atmosphere. The obtained nitrogen- and sulfur-doped porous carbons (NSPCs) possess 3D hierarchical porous structure and contain a significantly high amount of N and S species. The concurrent incorporation of N and S successfully modified the surface properties of carbon materials and lead to enhanced capacitive performance. The presented NSPC exhibits specific capacitance of 230 F g(-1) at a current density of 1 A g(-1) and showed excellent cycling stability, depicting a promising material for energy storage devices.

Impedance analysis and equivalent circuit modelling of cells subjected to sinusoidal vibration test using electrochemical impedance spectroscopy - Bangal, Ojas A.; Chaturvedi, Vikash; Babu, P. K. Ajeet; Shelke, Manjusha V. (2019 IEEE Transportation Electrification Conference (ITEC-India), 2019)
Electrochemical impedance spectroscopy is a multipurpose and non-destructive characterization technique in the analysis of electrochemical power sources such as Li-ion cells. The nyquist curve obtained by EIS spectrum of the cell gives information about its overall health. Curve fitting of the EIS nyquist plots further helps in determining the Equivalent Circuit Model (ECM) for a particular cell. In this paper commercial Li-ion cells from three different chemistries; Lithium Nickel Manganese Cobalt Oxide (NMC), Lithium Cobalt Oxide (LCO) and Lithium Iron Phosphate (LFP) are subjected to sinusoidal vibration test as per testing standard mentioned in United States Advanced Battery Consortium (USABC). The EIS measurement of the test cells have been carried out before and after the vibration tests. Curve fitting is carried out on the EIS plots and ECM for the cells is obtained. The components present in ECM and their actual values are estimated from the curve fitting analysis. The magnitude of various resistances like equivalent series resistance (R s ), charge transfer resistance (R ct ) and solid electrolyte interphase resistance (R sei ) is evaluated. This technique is also used in determining the capacitances inside the cell, mainly capacitance (C sei ) due to Solid Electrolyte Interphase layer (SEI) and capacitance due to double layer (C dl ) formation at electrode surface. The resistance in the cell is found to be increased and the capacitances values are decreased after vibration test. Bode plot for the cells are analysed and the overall change in the impedance of cell due to the vibration test is investigated as well. Scanning electron microscopy technique is used on cell electrodes, after vibration test, to validate the actual damage that took place within the cell. The study reveals that the EIS can be used as a non-destructive tool to check cell health after mechanical abuse.

Influence of the crystal plane orientation in enhancing the electrochemical performance of a trication-substituted cathode for Li-ion batteries - Shivamurthy, Bogalera Papaiah; Thripuranthaka, Marulasiddappa; Shelke, Manjusha V.; Nayaka, Girish Praveen (Energy and Fuels, 2024)
High-voltage spinel cathodes with low nickel are promising candidates for Li-ion batteries owing to their high energy and power density, thermal stability, and eco-friendliness. However, the high operating voltage (similar to 4.7 V) leads to the decomposition of electrolytes, structural disorder, and deterioration of the cathode-electrolyte interphase (CEI) as well as hinders practical capability. We have synthesized trication-substituted spinel cathode materials with exposed (111) crystal planes and truncated octahedral shapes. These materials have demonstrated high specific discharge capacity and high rate capability up to 1000 cycles with a voltage window of 3.5-5 V. The crystal plane orientation of these materials has been investigated using X-ray diffraction of electrodes and electron microscopic studies and correlated with the electrochemical performance of the surface plane of exposed cathode materials. Among the three synthesized materials, the LMNFA2 cathode has shown a specific discharge capacity of 109.29 mAh g(-1) at 1 C after 1000 cycles with a capacity retention of 76.3%, which is nearly equal to the previously reported dual-phase material with the same metal compositions.

In situ solid-state synthesis of nitrogen-enriched porous carbon nanosheets from petroleum coke for lithium-ion hybrid capacitors - Benoy, Santhi Maria; Das, Anoushka K.; Sarmah, Debashis; Pawar, Meenakshi; Shelke, Manjusha V.; Saikia, Binoy K. (Energy & Fuels, 2025)
Lithium-ion capacitors (LICs) have emerged as a next-generation energy storage technology, offering a unique balance between the high energy density of lithium-ion batteries and the fast charge-discharge capability of supercapacitors. However, the development of high-performance anode materials remains a major challenge due to the trade-off between capacity, rate capability, and long-term cycling stability. Herein, we report a novel in situ solid-state synthesis approach for the scalable production of nitrogen-enriched porous carbon nanosheets (mBG1) from petroleum coke, an abundant industrial byproduct. The hierarchical porosity and optimized nitrogen functionalities of mBG1 facilitate rapid lithium-ion diffusion, enhanced electronic conductivity, and robust structural stability. Electrochemical characterization in lithium-ion half-cells demonstrates an exceptional specific capacity of 388 mAh g-1 at 0.1 A g-1, with an outstanding capacity retention of 92.7% over 1000 cycles (261.2 mAh g-1) at 1 A g-1. To validate its practical applicability, a full LIC coin cell was fabricated using mBG1 as the anode and commercial super activated carbon (super AC) as the cathode, achieving a specific capacitance of 44 F g-1 at 1 A g-1, a high energy density of 93.29 Wh kg-1 at 0.5 A g-1, and an impressive power density of 20.34 kW kg-1 at 10 A g-1, with 74% capacitance retention after 5000 cycles. The integration of ultrahigh nitrogen doping, hierarchical porosity, and scalable synthesis techniques offers a new pathway for designing next-generation lithium-ion capacitors with enhanced efficiency, stability, and economic viability. These findings establish mBG1 as a high-performance, scalable, and sustainable anode material for next-generation LICs, offering a transformative pathway for the valorization of petroleum coke in advanced energy storage applications.

Investigations into the nucleation dynamics of the stable Na-metal anode: revealing the role of a tin-infused carbon nanofiber interlayer - Wasnik, Kundan; Yadav, Poonam; Ahuja, Manuj; Mirzapure, Vinay; Johari, Priya; Shelke, Manjusha V. (ACS Applied Materials & Interfaces, 2025)
Fundamental understanding and controlling of sodium nucleation are essential for enhancing the performance, safety, and longevity of sodium metal batteries, which is not yet clearly understood in the case of sodium metal batteries. The present study showcases how a modification in the host material influences nucleation kinetics. Current-time transient studies on copper, carbon nanofiber, and tin-embedded carbon nanofiber interlayers employing the Scharifker-Hills model elucidate the mode of nucleation. This work tries to delve deep and presents a case study on how a tin-based interlayer can not only minimize the barrier for sodium nucleation but also direct the sequential progressive and instantaneous nucleation of sodium metal while reducing the overpotential substantially, resulting in crystalline, uniform Na-metal deposition. Further, to account for the complex dynamics of solid electrolyte interphase (SEI) formation distinctly associated with alkali metal deposition, the SEI-fracture model has been included, and the quantification of electrochemical nucleation parameters is obtained. The results provide important insights into the sodium nucleation mechanism, paving the way to counter dendrite formation and SEI dissolution issues of the Na-metal anode.
Keywords: overpotential; progressiveand instantaneous nucleation; Scharifker-Hills model; SEI-fracture model; tin interlayer